Acetabular rim extension using a personalized titanium implant for treatment of hip dysplasia in dogs: short-term results - Kwananocha, Irin; Magré, Joëll; Willemsen, Koen; Weinans, Harrie; Sakkers, Ralph J. B.; How, Thijs; Verseijden, Femke; Tryfonidou, Marianna A.; van der Wal, Bart C. H.; Meij, Björn P. (Frontiers in Veterinary Science, 2023)
Hip dysplasia (HD) is a common orthopedic problem in young dogs. To decrease the laxity of the hip joint related to HD, the surgical treatments are recommended to increase femoral head coverage. ACEtabular rim eXtension (ACE-X) using a personalized 3-dimensional printed titanium shelf implant is a new surgical treatment to increase femoral head coverage and decrease laxity of the dysplastic hip joint, however, the efficacy is less know. Client-owned dogs older than 6 months with clinical signs of coxofemoral joint subluxation and radiographic evidence of HD with no or mild osteoarthritis (OA) were included. The Norberg angle (NA), linear percentage of femoral head overlap (LFO), and percentage of femoral head coverage (PC) were investigated radiographically and with computed tomography (CT) before and after surgery. OA was graded (scores 0–3) according to the maximum osteophyte size measured on CT. In addition, joint laxity (Ortolani) test results, gait analysis, and the Helsinki chronic pain index (HCPI) questionnaire were obtained at preoperative, immediately postoperative and at 1.5- and 3-month evaluations. Acetabular rim extension was performed in 61 hips of 34 dogs; NA, LFO, and PC were significantly higher immediately postoperatively and at the 1.5- and 3-month follow-up examinations compared with preoperative values (p < 0.05). Osteophyte size gradually increased over time (p < 0.05). The OA score significantly increased between preoperatively and directly postoperatively, and between preoperatively and at 3-month follow-up (p < 0.05). The laxity test normalized in 59 out of 61 hips after surgery, and the HCPI questionnaire showed that the pain score decreased significantly at 1.5 and 3 months, postoperatively. The force plate showed no significant improvement during the 3 months follow-up. Although pain reduction by the implant was unclear in short-term results, a personalized shelf implant significantly increased femoral head coverage and eliminated subluxation of the dysplastic hip joint. Further studies are required to study the long-term efficacy of gait, chronic pain, and progression of osteoarthritis.